Pengaruh Kualitas Produk dan Brand Image Terhadap Minat Beli Kamera DSLR Nikon Pada Mahasiswa Desain Komunikasi Visual (DKV) Universitas Negeri Padang - Danang Krismisandi; Rose Rahmidani (Jurnal Salingka Nagari, 2022)
The reason for this study was to examine the impact of item quality and brand picture on the buy expectation of Nikon DSLR cameras in visual correspondence plan (DKV) understudies at Padang State University. This kind of exploration is causative. The populace in this study were understudies of visual correspondence plan (DKV) Padang State University. The quantity of tests in this review were 97 individuals and were chosen utilizing the non-likelihood examining strategy with purposive inspecting method. The information utilized is the sort of essential information got through disseminating polls to visual correspondence plan understudies at Padang State University with foreordained rules. The scientific strategy utilized is various relapse examination utilizing SPSS 26.The outcomes showed that (1) item quality affected purchasing interest in DSLR cameras in visual correspondence plan (DKV) understudies at Padang State University, (2) brand picture altogether affected purchasing interest in DSLR cameras in visual correspondence plan (DKV) understudies at the Padang State Universitity